2014
DOI: 10.1093/humupd/dmu010
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of psychosocial factors associated with emotional adjustment in in vitro fertilization patients

Abstract: Whilst some psychosocial variables appear to be consistently associated with distress for IVF patients, two-thirds of the variables tested to date do not appear to be associated with emotional adjustment. This review highlights key psychosocial factors to assist the identification of patients at high risk of psychological distress. These findings highlight at least two psychological factors that may be amenable to alteration with psychological or educational interventions. Future work should explore whether ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 131 publications
8
93
1
6
Order By: Relevance
“…Alternatively, it could be argued that the SCREENIVF should (and did not) predict emotional maladjustment regardless of outcome, for example predict the level of anxiety in response to pregnancy (e.g., fear about miscarriage). A recent review confirmed the importance of the five risk factors of the SCREENIVF associated with emotional adjustment (53).…”
Section: Discussionmentioning
confidence: 88%
“…Alternatively, it could be argued that the SCREENIVF should (and did not) predict emotional maladjustment regardless of outcome, for example predict the level of anxiety in response to pregnancy (e.g., fear about miscarriage). A recent review confirmed the importance of the five risk factors of the SCREENIVF associated with emotional adjustment (53).…”
Section: Discussionmentioning
confidence: 88%
“…Certain psychosocial factors such as neuroticism and the use of escapist coping strategies, were identified in a recent systematic review as predisposing factors for increased risks of psychological distress, whilst an increased level of social support is protective [27]. The individual difference in sensitivity to stressors can account for the various aspects of stress and emotional adjustment in women undergoing assisted conception.…”
Section: Discussionmentioning
confidence: 99%
“…This work has shown conclusively, for example, that infertile individuals present normative psychological functioning, infertility is emotionally distressing, women react more negatively to infertility than men, and that the infertility experience can strengthen the marital relationship. There is also extensive information on individual differences that modify the intensity of the infertility experience (e.g., coping styles, marital factors, social support, and infertility beliefs) (26). Furthermore, reactions to the different stages of fertility treatment are now well documented, for instance, that the 2-week waiting period is the most stressful period of treatment (27) and that treatment failure is followed by strong negative emotional reactions (mainly depression) that may last for 6 months (28).…”
Section: Nurse Advocacy and The Psychological Sequelae Model Of Infermentioning
confidence: 99%